Leptin: A hormone linking activation of neuroendocrine axes with neuropathology. (January 2015) - Stieg, Mareike R.; Sievers, Caroline; Farr, Olivia; Stalla, Günter K.; Mantzoros, Christos S.
Highlights: Leptin has an influence on the four main neuroendocrine axes. It affects psychological functioning by effects on the central nervous system. By suppression of the HPA-axis, leptin could have anti-depressant like-effects. Affecting neuroplasticity, leptin may additionally act as pro-cognitive hormone. Summary: Leptin, a peptide hormone secreted by adipocytes, plays a central role in controlling appetite and weight in both rodents and humans. Basic science and clinical research suggest that this hormone not only affects the regulation of the neuroendocrine axes, but also exerts effects on the central nervous system with subsequent alterations in psychological functions. For instance, leptin suppresses cortisol secretion during stress-related activation of the adrenal axis. As psychiatric disorders like depression are associated with hypercortisolism, leptin is proposed to exert anti-depressant-like effects due to its inhibition of chronically overactive hypothalamo-pituitary-adrenal axis function. Moreover, leptin status of depressed patients could serve as a prognostic marker for therapy response. Besides its influence on neuroendocrine pathways leptin seems to have direct central effects on brain development and neuroplasticity. Low leptin levels have been shown to be associated with increased risk of developing dementia, supporting the idea of a pro-cognitive effect of leptin. These areas may have direct clinical implications and deserve to be studied further in the future.